Changes in age-specific seroprevalence of Japanese encephalitis virus and impact of Japanese encephalitis vaccine in Korea - Byung Ok Kwak; Young Jin Hong; Dong Hyun Kim (Clinical and Experimental Pediatrics, 2022)
The Japanese encephalitis (JE) virus is the leading cause of vaccine-preventable encephalitis in Asia. Since the introduction of a universal JE vaccination program and urbanization of Korea, the incidence of JE has dramatically decreased in Korea. However, recent JE cases have occurred, predominantly among unvaccinated adults and with a shift in age distribution. Here we aimed to review the changes in age-specific JE seroprevalence over time and discuss the implications of JE vaccination programs in Korea. Following the last epidemic in 1982–1983, mandatory vaccination for all children aged 3–15 years was conducted annually until 1994. However, JE has reemerged, predominantly affecting unvaccinated adults aged 40 years or older and demonstrating a shift in age distribution toward older populations. The age-specific seroprevalence of the JE virus in Korea has changed noticeably over time. Seropositivity in children and adolescents increased from 10%–59% in the 1970s to 90%–92% in the 1980s after the implementation of the JE vaccination program and increased further to 98% in 2012. No age-specific difference in the seroprevalence of JE was found, and appropriate levels of immunity to JE were maintained for all age groups. Continuous surveillance of the seroprevalence of JE is essential to establish a proper immunization policy in Korea.